Exploratory Google Trends study of user concerns about oral problems - Christian Renzo Aquino-Canchari; Brenda Sofia Caira Chuquineyra (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: More and more people search for health information on the internet and oral health is no exception.